HUBUNGAN KOORDINASI MATA DAN KAKI DAN POWER OTOT TUNGKAI DENGAN HASIL SHOOTING KE GAWANG DALAM TIM FUTSAL SMA NEGERI 1 SUNGAI APIT - Arifin, Muhammad; Slamet, Slamet; Mandan, Ali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine whether there is a relationship between eye and foot coordination and leg muscle power with the results of shooting into the goal in the futsal team of SMA NEGERI 1 Sungai Apit, Sungai Apit District, Siak Regency. The sample of this research is the futsal team of SMA NEGERI 1 Sungai Apit, Sungai Apit District, Siak Regency, totaling 16 people. The sampling technique was taken (total sampling) or the full sampling technique of the futsal team at SMA NEGERI 1 Sungai Apit, Sungai Apit District, Siak Regency, totaling 16 people. The results of the correlation of the futsal team at SMA NEGERI 1 Sungai Apit, Sungai Apit District, Siak Regency where the first analysis is between X1 and Y where rtab is at a significant level É‘ (0.05) = r_hitung (0.880)> r_tab (0.514), meaning that the hypothesis is accepted and there is a strong relationship between X1 and Y. From the calculation of the second analysis of X2 and Y, where r_tab is at a significant level É‘ (0.05) = means r_count (0.791)> r_tab (0.514), meaning that the hypothesis is accepted and there is a strong relationship between X2 and Y. and X2 with Y, where rtab is at the significant level É‘ (0.05) = r_count (0.880)> r_tab (0.514), it can be concluded that the relationship between X1 and X2 and Y is very strong. Key Words: Eye and Foot Coordination, Leg Muscle Power and Shooting Results to the goal.